Perubahan Pola Pergerakan pada Simpang Kalibanteng akibat Penerapan Manajemen Dua Arah pada Flyover - Wicaksono, Y I; Indriastuti, Amelia Kusuma; Riyanto, Bambang (Department of Civil Engineering, Diponegoro University, 2017)
Kalibanteng Intersection is one of primary node in west part of Semarang City. It is a signalized intersection which shaped roundabout. It lies on the truck track from west to east of Java Island, which is crossed over by Flyover Yos Sudarso – Siliwangi and Flyover Sudirman – Siliwangi. Formerly, the flyover is designed for Siliwangi – Yos Sudarso vice versa. The flyover could decrease truck volume from east to west, on the contrary heavy vehicle movement is still overburden Kalibanteng Intersection capacity. On 2018, it is planned that Ahmad Yani Airport access road will be diverted. Thus, it is important to increase Kalibanteng Intersection performance, and accommodate the airport access divertion plan at a time. This research is aimed to identify the existing movement pattern at Kalibanteng Intersection, to evaluate the existing signalized intersection performance, to develop a simulation of two way management on Kalibanteng Flyover, to analyze the movement pattern due to the implementation of two way management on the flyover, and to analyze the signalized intersection due to this management. The results show that the highest movements in Kalibanteng Intersection are the movement from Siliwangi to Yos Sudarso (which is dominated by heavy vehicle) and from Siliwangi to Sudirman (which isi dominated by light vehicle and motorcycle), and will keep on increasing in the future. These movement greatly contribute on intersection performance. This shows that the utilization of the flyover for two-way movement can be considered with mode type limitation. Using two-way flyover, the performance of Kalibanteng signalized intersection will increase.